Evaluation of Priority Fodder Trees for Leaf Yield and Nutritional Value at Arba Minch, Ethiopia - Habtamnesh Adane; Agena Anjulo (International Journal of Forestry Research)
Tree fodder is an important supplement to livestock feed particularly where the shortage of palatable herbaceous biomass affects the animal production in dry seasons. In Arba Minch and nearby semiarid parts of southern Ethiopia, lopping and feeding tree fodder is becoming a common practice to increase livestock productivity. However, knowledge of the fodder species’ biomass productive potential and their nutritional content along with their digestibility is limited. Hence, this study investigated leaf yield, nutritional value, and chemical composition including mineral profile and in vitro dry matter (DM) and organic matter (OM) degradability of these three browse tree species viz., Dendrocalamus giganteus, Balanites aegyptiaca, and Terminalia brownii. These are commonly used trees for lopping branches and harvesting fodder in Arba Minch, southern Ethiopia. The leaf yield of the trees was assessed based on the uniformity in tree parameters such as height, diameter at breast height, and crown spread. Samples of tree leaves were analysed for chemical composition using standard procedures. The results indicated that fodder yield lopped from all branches was 25.92 kg·DM/five culms for D. giganteus, 19.60 kg·DM/tree for B. aegyptiaca, and 22.53 kg·DM/tree for T. brownii. The crude protein (CP) content was 69.3 g/kg·DM, 113.2 g/kg·DM, 102.6 g/kg·DM, and 122.7 g/kg·DM for the forage hay, D. giganteus, B. aegyptiaca, and T. brownii, respectively. Among the studied browse species, Terminalia brownii leaf fodder constitutes greater potential to supply CP, IVDMD (48.43%), and IVOMD (56.39%) for ruminants. Mineral contents of the trees fodder were also in the suitable optimal range to support ruminant livestock performance except for zinc which was below the recommended level.